Regular hospital visits improve the prognosis of hepatocellular carcinoma after initial diagnosis: A single regional community hospital study - Watanabe, Masaaki; Yomokori, Hiroaki; Takahashi, Yoshihito; Minamino, Tsutomu; Kubo, Hidefumi; Okada, Takemichi; Yamazaki, Hitoshi; Shibuya, Akitaka; Koizum, Wasaburo (Turkish Journal of Gastroenterology, 2017)
Abstract Background/Aims: The aims of this study were to investigate the relationship between regular hospital visits and prognosis of hepatocellular carcinoma (HCC) and to suggest methods to avoid poor prognoses in HCC. Materials and Methods: In total, 103 patients with initial HCC were classified into 3 groups based on hospital visits occurring 1 year before diagnosis: group A was patients with regular hepatologist visits (n=41), group B was those with regular visits to other hospital divisions (n=50), and group C was those with no hospital visits (n=12). The relationships between the 3 groups and survival rates, backgrounds, hepatic reserve, and stages of HCC were analyzed. Results: Survival rates of groups A, B, and C after diagnosis at 36 months were 77.9%, 66.3%, 31.3%, respectively. These were significantly higher in group A than in B and in group B than in C (p=0.042 and p=0.003, respectively; generalized Wilcoxon test). Child-Pugh classification, Japan integrated staging (JIS) score, and Barcelona clinic liver cancer (BCLC) staging were poor in group C compared with group A (p Conclusion: Hepatologist visits appeared to improve the prognosis of initial HCC. Males and non-virally infected patients should be screened to avoid delays in diagnosis. Since cases of non-viral HCC are likely to increase in Japan, surveillance methods for all clinicians should be established. Cite this article as: Watanabe M, Yomokori H, Takahashi Y, et al. Regular hospital visits improve the prognosis of hepatocellular carcinoma after initial diagnosis: A single regional community hospital study. Turk J Gastroenterol 2017; 28: 353-60.